2019
DOI: 10.1039/c9ob01134j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of α-CF3-proline derivatives by means of a formal (3 + 2)-cyclisation between trifluoropyruvate imines and Michael acceptors

Abstract: The first (3 + 2)-cyclisation of 3,3,3-trifluoropyruvate-derived imines and indandione-based Michael acceptors giving spirocyclic α-CF3-α-proline derivatives was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The preparation of spirocyclic compounds has garnered considerable interest in recent years as these motifs have gained greater significance as medicinally relevant scaffolds ( Scheme 17 ) [ [76] , [77] , [78] , [79] , [80] ]. Waser and co-workers disclosed the synthesis of spirocyclic fluorinated proline derivatives in 2019 [ 81 ]. To achieve this, a (3 + 2)-cyclisation approach under phase transfer conditions was implemented.…”
Section: Complex Fluorine-containing Aromatic Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of spirocyclic compounds has garnered considerable interest in recent years as these motifs have gained greater significance as medicinally relevant scaffolds ( Scheme 17 ) [ [76] , [77] , [78] , [79] , [80] ]. Waser and co-workers disclosed the synthesis of spirocyclic fluorinated proline derivatives in 2019 [ 81 ]. To achieve this, a (3 + 2)-cyclisation approach under phase transfer conditions was implemented.…”
Section: Complex Fluorine-containing Aromatic Amino Acidsmentioning
confidence: 99%
“…For example, an additional fluorine was successfully incorporated to give compound 72b in 40 % yield.
Scheme 17 Synthesis of spirocyclic fluorinated amino acids, Waser and co-workers [ 81 ].
…”
Section: Complex Fluorine-containing Aromatic Amino Acidsmentioning
confidence: 99%
“…We have recently shown that preformed imines 4 undergo highly diastereoselective (3+2)‐type cyclizations with Michael acceptors to access CF 3 ‐proline derivatives 6 , with the α‐position acting as the donor site . Based on these observations, we now became interested in developing this concept further towards a more general approach to access (novel) acyclic α‐CF 3 ‐α‐amino acid derivatives in an unprecedented fashion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to using imines as acceptors for nucleophilic additions, the last years saw an increasing number of reports demonstrating that the inherent reactivity of imines can be inverted (making the imine carbon nucleophilic). Such an imine umpolung can be achieved by using a suited benzylamine protecting group that allows for the formation of ambident nucleophilic azaallyl anions under basic reaction conditions, which then preferably react with electrophiles in the α‐position (compare with Scheme B) . Accordingly, these umpolung approaches allow for the synthesis of valuable acyclic, or cyclic, products by starting from easily accessible imines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation